The co-occurrence of multiple sclerosis and Evans syndrome: A case report - Mohammad Ali Sahraian; Saeideh Salehizadeh; Abdorreza Naser Moghadasi (Babol University of Medical Sciences, 2020)
Background: Evans syndrome is an uncommon autoimmune disorder manifested by fatigue, jaundice, pallor, purpura and petechiae. The main characteristics of this rare disease are simultaneous or sequential existence of positive anti-globulin test, immune thrombocytopenia (ITP) and autoimmune hemolytic anemia (AIHA). Evans syndrome as an autoimmune disorder can be associated with other diseases. The concomitancy of Evans syndrome and multiple sclerosis (MS) has not been reported so far. In this case study, a - 21-year old male with concomitant Evans syndrome and MS has been reported. Case Presentation: A 21-year-old male of Iranian origin and known case of Evans syndrome, was referred to our hospital for better evaluation. Evans syndrome was presented with acute jaundice, purpura, petechiae, and easy bruising when he was 9.He was under treatment of corticosteroid and cytotoxic agents, and presented with left lower extremity paresis for 5 months before admission to our hospital. According to neuroimaging and pathologic results, multiple sclerosis (MS) was diagnosed. Hence, we decided to treat the patient with rituximab. The patient has been stable without any further exacerbation or increase in disability progression after 2 years from diagnosis. Conclusion: Evans syndrome can be associated with other autoimmune disorders. For our case, we have reported this association with MS.